The renaissance of photodynamic therapy for early esophageal cancer: is it the time? - Fiorelli, Alfonso; Prencipe, Aldo; Santini, Mario (Journal of Thoracic Disease, 2018)
Early esophageal cancer is a superficial tumor limited to the mucosal layers of the esophagus. In the last decade, the increased use of endoscopic surveillance in asymptomatic patients has contributed to an increased proportion of patients with early esophageal cancer (1).